Respostas

  • Usuário do Brainly
2014-07-09T20:13:20-03:00
G)
 \frac{2 m^{2} }{3} - \frac{m}{2} +1- \frac{m^{2} }{2} + \frac{2m}{3} -1=

mmc de tudo

 \frac{4 m^{2}-3m+6-3 m^{2} +4m-6 }{6} =

 \frac{ m^{2} }{6} + \frac{m}{6}

h)
 \frac{m}{2} - \frac{mn}{3} +2+mn+1- \frac{m}{2} =

mmc de tudo

 \frac{3m-2mn+12+6mn+6-3m}{6} =

 \frac{4mn}{6} + \frac{18}{6} =

 \frac{2mn}{3} +3


i)
2a b^{2} - \frac{ a^{2}b }{3} - \frac{3a b^{2} }{4} + a^{2} b=

mmc de tudo

 \frac{24a b^{2}-4 a^{2}b-9a b^{2} +12 a^{2} b  }{12} =

 \frac{15a b^{2} }{12} + \frac{8 a^{2}b }{12} =

 \frac{5a b^{2} }{4} + \frac{2 a^{2}b }{3}
AS letras são iguais ...os expoentes diferentes...não pode juntar.
ah, vlw
Entendeu direitinho?
sim hueuhue vlw msm cara
Ótimo!